Mental health in the construction industry: an interview with Australia's MATES in construction CEO, Jorgen Gullestrup. (1st October 2020) - Neis, Barbara; Neil, Kerri
ABSTRACT: Research in Australia and internationally indicates that construction work is linked to higher suicide rates. Higher rates are associated with irregular, intense and remote working, as well as labour force demographics. Through the organization MATES in Construction, the Australian construction sector has become a world-leader in researching and seeking to address the problem of suicide in the sector. This contribution is an edited version of an interview carried out between the lead author and Jorgen Gullestrop, CEO of Mates in Construction in Queensland and Northern Territory, Australia. The interview took place during Jorgen's February 2020 visit to Newfoundland and Labrador (NL), Canada, on the opposite side of the world. There has been very little research or active mobilization around suicide in construction in Canada. During his visit, Jorgen spent a week with the NL Construction Safety Association's membership. The interview provides important insights into the Australian construction industry as it operated when Jorgen first came to Australia from Denmark in the 1980s. It also provides insights into the structure of the industry today, including how it is organized around precarious employment. Jorgen touches on the origins of MATES, how the MATES program works, and why, although Jorgen came out of the union movement, MATES was established as an independent charity separate from employers and unions. The interview includes reflections on gender, suicide and MATES, and on the importance of academic research to the MATES agenda.